HUBUNGAN PENGETAHUAN IBU TENTANG ASI EKSLUSIF DAN TINDAKAN IMD DENGAN STATUS PEMBERIAN ASI EKSLUSIF DI DESA BANDAR KLIPPA KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG TAHUN 2015 - Zulia Avriska Daulay; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
One effort to reduce infant morbidity and mortality is to give exclusive breastfeeding. WHO and UNICEF suggest giving breastfeeding exclusively to the baby until was six months. The success of breastfeeding is influenced by the mother's knowledge about breastfeeding. Alongside mother's knowledge, early initiation of breastfeeding also can determine the success of exclusive breastfeeding. This study aimed to determine the relationship of the level of mother's knowledge about exclusive breastfeeding and early initiation of breastfeeding action against the status of exclusive breastfeeding in Desa Bandar Klippa, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang. Type of this research was a analytic survey with crossectional design. Analysis data used chi-square test and the sample of research were 73 mothers that have baby with aged 7-12 months. The results showed that there was relationship between mother's knowledge with exclusive breastfeeding status (p = 0.014) and there was correlation between early initiation of breastfeeding action with exclusive breastfeeding status (p = 0.034). The results of research are expected to health workers to improve the promotion of exclusive breastfeeding and support to do early initiation of breastfeeding after maternal and do not encourage mothers to give milk formula instead of breast milk. Keywords: Mother’s Knowledge, Action Early Initiation of Breastfeeding; Exclusive breastfeeding status